2010
DOI: 10.1371/journal.ppat.1001176
|View full text |Cite
|
Sign up to set email alerts
|

Zn2+ Inhibits Coronavirus and Arterivirus RNA Polymerase Activity In Vitro and Zinc Ionophores Block the Replication of These Viruses in Cell Culture

Abstract: Increasing the intracellular Zn2+ concentration with zinc-ionophores like pyrithione (PT) can efficiently impair the replication of a variety of RNA viruses, including poliovirus and influenza virus. For some viruses this effect has been attributed to interference with viral polyprotein processing. In this study we demonstrate that the combination of Zn2+ and PT at low concentrations (2 µM Zn2+ and 2 µM PT) inhibits the replication of SARS-coronavirus (SARS-CoV) and equine arteritis virus (EAV) in cell culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
849
0
26

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 808 publications
(887 citation statements)
references
References 48 publications
(125 reference statements)
12
849
0
26
Order By: Relevance
“…Additionally or alternatively, Zn could also impair stages of viral replication that follow the release of TGEV into the cytoplasm. A possible intracellular target for Zn-mediated inhibition is the viral RNA polymerase which was reportedly inhibited by increasing intracellular Zn ions in case of the SARS-Coronavirus (SARS-CoV) and other viruses (te Velthuis et al, 2010). In our study, the relative amount of viral Sprotein RNA detectable in infected cells was significantly reduced by Zn treatment for 1-4 hpi without previous inhibition of virus penetration as shown in Fig.…”
Section: Resultssupporting
confidence: 56%
“…Additionally or alternatively, Zn could also impair stages of viral replication that follow the release of TGEV into the cytoplasm. A possible intracellular target for Zn-mediated inhibition is the viral RNA polymerase which was reportedly inhibited by increasing intracellular Zn ions in case of the SARS-Coronavirus (SARS-CoV) and other viruses (te Velthuis et al, 2010). In our study, the relative amount of viral Sprotein RNA detectable in infected cells was significantly reduced by Zn treatment for 1-4 hpi without previous inhibition of virus penetration as shown in Fig.…”
Section: Resultssupporting
confidence: 56%
“…In addition to the recent patents, the focus of this review article, there are papers describing potential therapeutic agents such as nucleic acids aptamers targeting helicase [94,95] and inhibitors of RdRp [96], which should not be ignored. However, most of the patents describe the agents for treatment or prevention of SARS based on in vitro and/or cell-based experiments, but few of them have been actually tested in animals and none in humans.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Therefore, successful supplementary strategies should include antiviral drugs and immune-modulation therapies (Benfield et al, 2002;Du et al, 2011;Han et al, 2009;Jiang et al, 2010;Karuppannan et al, 2012;Keirstead et al, 2008;Kreutz & Ackermann, 1996;Li et al, 2009;Opriessnig et al, 2011;Patel et al, 2008;te Velthuis et al, 2010;van der Meer et al, 2007;Wei et al, 2011;Yang et al, 2013;Zhuge et al, 2012). When evaluating the antiviral effect of tilmicosin against PRRSV, our data suggested that tilmicosin would be effective in reducing the PRRSV loads in vivo.…”
Section: Discussionmentioning
confidence: 73%
“…These data indicate that reducing the PRRSV load in the serum may prevent pigs from developing clinical signs after PRRSV infection. Several studies have attempted to identify effective anti-PRRSV treatments in vitro and in vivo (Benfield, Chase, Moore, Wagner, & Zeman, 2002;Du, Yoo, Paradis, & Scherba, 2011;Han, Fan, Patel, & Zhang, 2009;Jiang, Fang, Luo, Xiao, & Chen, 2010;Karuppannan, Wu, Qiang, Chu, & Kwang, 2012;Keirstead, Lee, Yoo, Brooks, & Hayes, 2008;Kreutz & Ackermann, 1996;Li et al, 2009;Opriessnig et al, 2011;Patel et al, 2008;te Velthuis et al, 2010;van der Meer et al, 2007;Wei et al, 2011;Yang et al, 2013;Zhuge et al, 2012). However, there are no effective commercial drugs available to prevent PRRSV infection in pigs in vivo.…”
Section: Introductionmentioning
confidence: 99%